Multiple Consecutive Cervicovaginal Cytology Specimens Confirm Persistent Colonization by Cokeromyces recurvatus: Case Report and Literature Review - Keng Lor; Christopher P. Hartley; Bobbi S. Pritt; Anna M. Kemp; Amy A. Swanson; Charles D. Sturgis (Case Reports in Pathology)
The published literature on cervicovaginal cytology includes fewer than ten reported cases of Cokeromyces recurvatus identified in Pap test samples. We report a unique case of an asymptomatic 27-year-old female with persistent gynecologic tract colonization by C. recurvatus in which distinctive fungal microorganisms were identified in three samples collected over three consecutive years.